PERAN PARTNERSHIP STRATEGY UNTUK MENINGKATKAN KINERJA PERUSAHAAN (Studi Pada Bank Perkreditan Rakyat di Provinsi Bali) - Ni Nyoman Kerti Yasa (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
The background of this research is the phenomena of increasing competition intensity in the industry of Bank Perkreditan Rakyat (BPR) in Bali. These phenomana will decrease the performance achievement of BPR compared to other micro financial institutions like Lembaga Perkreditan Desa. It is expected to overcome the problem of performance achievement degradation by implementing partnership strategy. This research is aimed to analyze the relation between variables, so that this can be grouped as explanatory research. This research takes place in Bali Province with the populations target are Bank Perkreditan Rakyat (BPR). The population of this research are 143 BPR in Bali Province by using non proportionate random sampling. There are 105 BPR in Bali province are choosen as the samples based on Kracjie and Morgan Table. The respondents are Head Director of each BPR, who understand about the industry competitive environment, partnership strategy, and performance. The statistic analysis used to analyze the hypothesis is Structural Equation Model (SEM). The result of analysis shows that tight industry competition will decrease the corporate performance; meanwhile this negative influence can be diminished if the partnership strategy is applied by the corporate.